Določanje statičnega in dinamičnega modula elastičnosti bukove vezane plošče - Merhar, Miran (Les (Ljubljana), 2020)
The study compared the values of the dynamic and static modulus of elasticity of 7- and 11-layer plywood with different combinations of the grain orientation of individual veneer layers. The dynamic modulus of elasticity was determined from the natural frequencies of the first and second vibration mode using the Bernoulli-Euler equation and the static modulus was determined using the 4-point bending test. The results showed that the plywood has the highest modulus of elasticity at the orientation of the wood grain of the outer layer 0°, and then the modulus decreases with increasing angle. The dynamic modulus is on average 12% higher than the static modulus for 7-layer boards and 14% higher for 11-layer boards. The dynamic modulus determined from the second natural frequency is equal to the modulus determined from the first natural frequency when there is no shear influence, but when the shear influence occurs, the value of the modulus decreases. From the above mentioned investigations it can be confirmed that both static and dynamic methods are suitable for determining the modulus of elasticity of plywood samples, but it is necessary to check the shear influence in the dynamic method.
Keywords: beech; bukev; modul elastičnosti; modulus of elasticity; nihanje; plywood; shear; static test; statični test; strig; vezana plošča; vibration